2001
DOI: 10.1002/eat.1096
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa, diabetes mellitus, brain atrophy, and fatty liver

Abstract: An increased number of diabetes mellitus cases followed by the development of anorexia nervosa have been reported. In this report, the opposite has been observed in the case of a patient with anorexia nervosa who later developed insulin-dependent diabetes mellitus, associated with brain atrophy and fatty liver. The patient was treated with insulin, amitriptylene, and behavior modification. Significant improvement was noted on this regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…In modern medicine, no satisfactory effective therapy is till available to cure the diabetes mellitus. Though insulin therapy is also used for the management of diabetes mellitus but there are several drawbacks like insulin resistance (Piedrola et al, 2001), anorexia nervosa, brain atrophy and fatty liver (Yaryura-Tobias et al, 2001) after chronic treatment. In recent years, there has been renewed interest in plant medicine (Dubey et al, 1994;Prince et al, 1998;Ladeji et al, 2003) for the treatment against different diseases as herbal drugs are generally out of toxic effect (Geetha et al, 1994;Rao et al, 2003) reported from research work conducted on experimental model animal.…”
Section: Introductionmentioning
confidence: 98%
“…In modern medicine, no satisfactory effective therapy is till available to cure the diabetes mellitus. Though insulin therapy is also used for the management of diabetes mellitus but there are several drawbacks like insulin resistance (Piedrola et al, 2001), anorexia nervosa, brain atrophy and fatty liver (Yaryura-Tobias et al, 2001) after chronic treatment. In recent years, there has been renewed interest in plant medicine (Dubey et al, 1994;Prince et al, 1998;Ladeji et al, 2003) for the treatment against different diseases as herbal drugs are generally out of toxic effect (Geetha et al, 1994;Rao et al, 2003) reported from research work conducted on experimental model animal.…”
Section: Introductionmentioning
confidence: 98%
“…Oxidative stress induced by chronic hyperglycemia has been associated with dysfunction and apoptosis of several cell types, including pancreatic β cells, endothelial cells, neurons, and glial cells, indicating that hyperglycemia and oxidative stress promote the progression and complications of this disease (14). Although, insulin therapy is also used for the management of DM, there are drawbacks of insulin resistance, anorexia nervosa, brain atrophy, and fatty liver (30). The World Health Organization recommended the use of plants as an alternative therapy for diabetes (29).…”
Section: Introductionmentioning
confidence: 99%
“…[24] Available drugs and insulin injection used for the management of hyperglycemia associated with the diabetic state come with undesirable side effects. [22,[25][26][27] The undesirable side effects and high cost of anti-diabetic drugs have led to the search for plants with hypoglycemic properties for the management of DM. [28,29] Several plant species of medicinal values have been previously investigated for hypoglycemic properties.…”
Section: Introductionmentioning
confidence: 99%